Therapeutic complement inhibition: new developments - Emlen, Woodruff; Li, Wenhan; Kirschfink, Michael (Seminars in thrombosis and hemostasis, 2010)
Activation of the complement system significantly contributes to the pathogenesis of various acute and chronic inflammatory diseases. Current strategies to inhibit complement include the replacement or substitution of endogenous soluble complement inhibitors (e.g., C1 inhibitor [C1 inh], recombinant soluble complement receptor 1, TP10), the administration of antibodies to block key proteins of the cascade reaction (e.g., C5) or to neutralize the action of the complement-derived anaphylatoxins, or blockade of complement receptors (e.g., C5aR, CD88). The recent approvals of anti-C5 for the treatment of paroxysmal nocturnal hemoglobinuria as well as of C1 inh for the treatment of hereditary angioedema beyond European countries have provided a resurgence of interest in the potential of complement therapeutics for the treatment of disease.
Gesehen am 18.06.2021